Network Automation With Multithreading Using GNS3 and Netmiko - Gondhalekar, Bharati; Manna, Himadri; Kothi, Shreyash; Borsae, Dipak Balu (Indian Journal of Computer Science, 2024)
In the field of network automation, the combination of powerful tools like Netmiko and simulation environments like GNS3 offers network engineers an unprecedented opportunity to streamline operations, improve time efficiency, and enhance reliability. In this research we have done the automation in network configuration and also automation in backup of configuration. Configuration backup plays a crucial role in networking as it facilitates rapid failure recovery, reduces downtime, and enhances security. However, the backup process can be time-consuming, which is why a multithreading approach is adopted. This project focuses on exploring the utilization of Netmiko, a Python library for network device management within the GNS3 platform to automate various networking tasks. By creating a simulated network environment and developing Python scripts that leverage Netmiko, this project demonstrates the automation of configuration and OSPF routing protocol. Furthermore, the project investigates the multithreaded configuration backup and conducts a performance time analysis between multithreading and single-thread backup configurations. The objective of this study is to contribute further to current research on network automation.